A detailed analysis of the imperfections of pulsewidth modulated waveforms on the output stage of a class D audio amplifier - Koeslag, Francois (Stellenbosch : University of Stellenbosch, 2009)
Thesis (PhD (Electrical and Electronic Engineering))--University of Stellenbosch, 2009.